ABILITY OF ACCOUNTING DATA TO PREDICT STOCK RETURNS OF NON-FINANCIAL INSTITUTIONS IN TURKEY - Touray, Saikou; Nasution, Damai (BAKI (Berkala Akuntansi dan Keuangan Indonesia), 2023)
This study uses panel data of the top 10 non-financial companies in Turkey to analyze the impact of accounting information in predicting stock returns for period 1998 to 2019. The rationale behind choosing non-financial firms is based on the believed that financial firms have their own ways of financing and examining together with financial firms may reveal biased result. The panel least square is employed, the analysis revealed that only financial leverage, earning per share and growth opportunities have the capability of predicting stock returns in Turkey. Moreover, the outcome also revealed that a 1% increase in leverage will decline stock returns by 1.07%. On the other hand, earning per share and growth opportunity have positive effects on stock returns at 1% and 5% levels of significance, respectively. This implies that a 1% increase in earnings per share and growth opportunity will lead to an increase in stock returns by 1.8% and 2.1% respectively. However, capital expenditure and firm size are unable to predict stock returns.